Marine fishes (Elasmobranchii and Teleostei) from the Santana Archipelago, a Marine Protected Area in the southwestern Atlantic. Issue 8 (14th September 2017) - Bauer, Arthur de Barros; Gomes Fischer, Luciano; Di Dario, Fabio; Mincarone, Michael Maia
ABSTRACT: The Santana Archipelago (22°23′S, 41°42′W) is located at the northern limit of the South Brazil Bight in Southeastern Brazil, a major topographic feature of the South American continental shelf relevant in terms of fisheries, biogeography and conservation. Herein, the first inventory of the ichthyofauna of the Santana Archipelago is presented, with information on the distribution and conservation status of 147 species of the Teleostei and Elasmobranchii. Sampling was performed during 15 field expeditions between March 2013 and November 2015. A total of 6931 specimens were collected using bottom trawl, beach seine, hand net and scuba diving. Records of 28 species were based on photographs, and five species were recorded through underwater sighting. The Elasmobranchii was represented by nine species in eight families and six orders, and the Teleostei by 138 species in 54 families and 26 orders. Previous records of fishes from the Archipelago consist of 18 species deposited in fish collections; therefore, 129 species are reported herein for the first time. Most (114, 77.5%) species have large geographic distributions (western Atlantic: 81 species, 55.1%; eastern and western Atlantic: 33 species, 22.4%), but seven recorded species (4.8%) are endemic to the Brazilian Province. At the Global (IUCN) level, 12 species (8.1%) are threatened with extinction. Thirteen (8.8%) species are also considered as threatened at the Regional (Brazilian) level . These results highlight the relevance of the Santana Archipelago in the Brazilian conservationist context. Possible threats to the ichtyofauna of the Archipelago are discussed, and effective measures of conservation are presented.